Monopsony in local labour markets - Manning, A; Petrongolo, B (Oxford University Press, 2024)
We investigate employer monopsony power in local labour markets in the UK. We propose a model in which market power stems from idiosyncratic worker preferences over non-wage attributes of jobs, including the commuting distance. This set-up delivers point-specific, overlapping local labour markets. The resulting concentration index reflects the intensity of commuting flows between local areas, and is lower than the conventional index based on self-contained, non-overlapping areas because commuting across local areas expand workers’ outside options. We estimate that employment concentration in local labour markets was slightly falling over the past 2 decades. The model-based concentration index is negatively correlated to local wages and performs better than other purely local concentration measures. However, in quantitative terms, the observed fall in concentration can predict only a negligible increase in wages.